Efeito cicatrizante e anti-inflamatório de formulações contendo Jacaranda decurrens CHAM - SERRA, Mariana Barreto (2017)
Jacaranda decurrens CHAM. (Bignonaceae), known as carobinha, is prevalent in the cerrado biome and presents popular use as an anti-inflammatory and wound healing. In this study, investigate the healing and anti-inflammatory effects of topical (FTEHJ) and oral (FoEHJ) formulations prepared from the hydroalcoholic extract of the leaves of J. decurrens. Preliminary phytochemical evaluation was carried out. In the healing test, 55 Swiss mice were submitted to a dorsal lesion of 1 cm in diameter and treated topically with formulation base (BFt), Fibrinase® ointment and FtEHJ (50mg/kg). At the end of the treatment periods, the animals were euthanized and the scar tissue was removed for dosage of inflammatory cytokines (TNF-α, IL- 1β, and IL-6) by ELISA on the first and seventh day of analysis, TGF-β gene expression, type I collagen and type III collagen on the seventh day and histological evaluation on the ninth day. For the inflammation assay 40 rats were used, divided into the following groups: Vehicle, Carrageenan (1%), Carrageenan + Indomethacin (10mg / kg), Carrageenan + FoEHJ (250mg / kg). After 4h of the application of carrageenan there was a withdrawal of ascitic fluid for global and differential leukocyte count. The phytochemical evaluation showed a strong presence of phenolic compounds, flavonoids and condensed tannins. The FtEHJ group had a greater percentage of wound contraction (18%) within the first 24 hours of treatment and healing acceleration for nine days, while the BFt and Fibrinase® groups healed within 12 days. In addition, it presented lower inflammatory cytokine content and greater gene expression of TGFβ and type I collagen. A histological analysis showed discrete inflammation, epithelization and marked collagen content. Treatment with a FoEHJ inhibited neutrophil migration by 72% whereas the indomethacin group inhibited by 56%, compared to the carrageenan group (2040 ± 244.8 neutrophils / mm3). It is believed that as actions of flavonoids and phenolic compounds, present not hydroalcoholic extract of J. decurrens, be related to the cicatrizant and antiinflammatory activities of the formulations.